PERLINDUNGAN HUKUM TERHADAP ANAK SEBAGAI KORBAN EKSPLOITASI SEKS KOMERSIAL ANAK DI KEPOLISIAN SEKTOR TENAYAN RAYA KOTA PEKANBARU - Destanesia, Annisa; Firdaus, Emilda; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
One type of sexual crime that afflicts children is the commercial sexual exploitation of children, children to work as commercial sex workers to benefit as a livelihood. Have been many cases of sexual exploitation of children is happening, but very limited (few) are revealed, this is because most of the children who are victims of tough questioning and tend to shut down (shame).The research objective of this thesis, namely; First, to determine the legal protection of children as victims of commercial sexual exploitation of children in the Police Sector Tenayan Raya Pekanbaru. Second, to determine the constraints in providing legal protection of children as victims of commercial sexual exploitation of children Tenayan Police Sector Raya Pekanbaru. Third, to know the effort in overcoming obstacles in providing legal protection for children as victims of commercial sexual exploitation of children in the Police Sector Tenayan Raya Pekanbaru. This type of research is sociological research, studies show the unity between law and society with the gap between das sollen and das sein.From the research, there are three basic conclusions. First, the legal protection of children as victims of commercial sexual exploitation of children has not been effective, because of the punishment meted out to the perpetrators did not provide a deterrent effect so that these crimes continue to happen until now. Second, the constraints experienced by the Police in providing legal protection, among others, the lack of reports from the public, the victim tough questioning and the unavailability of special detention room of children and women in the Police Sector Tenayan Raya Pekanbaru. Third, efforts to overcome the obstacles in the police, among others, working together with the community to be willing to provide information about the crime that occurred, increasing the number of active police personnel, in collaboration with child protection agencies. Suggestions Author, First, it is expected that the punishment meted out to the perpetrators can provide a deterrent effect so as to reduce the criminal activity of commercial sexual exploitation of children. Secondly, it is expected that the Police Sector Tenayan Raya Pekanbaru can cooperate with society to provide information about the crime that happened. Thirdly, it is expected that the efforts made by the police and Child Protection Institution can run optimally and as expected.Keywords: Legal Protection - Children - Sexual Exploitation Commercial